1996
DOI: 10.1111/j.1365-294x.1996.tb00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of transgenic plant marker gene persistence in soil microcosms

Abstract: Genetic engineering offers the opportunity to generate plants with useful new traits conferred by genes originating from a variety of organisms. The objectives of this study were to establish methods for investigating persistence of recombinant plant marker DNA after introduction into soil and to collect data from controlled laboratory test systems. As a model system, we studied the stability of DNA encoding recombinant neomycin phosphotransferase II (rNPT‐II), a neomycin/kanamycin resistance marker, used in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 36 publications
5
104
0
2
Order By: Relevance
“…As was the case with eDNA transport, much of study of eDNA persistence has been motivated by concern over the release of transgenes from genetically modified organisms. Such studies have examined persistence of genes from transgenic crops in terrestrial soils (Widmer et al 1996(Widmer et al , 1997Hay et al 2002;Gebhard and Smalla 2006) and nearby groundwater and riverine environments (Matsui et al 2001;Zhu 2006). Across these studies, transgenic material remained detectable for long periods of time (days to years) in terrestrial soils, but much shorter periods of detection (hours to days) occurred in aquatic environments (Table 1).…”
Section: Fate: What Factors Influence Edna Persistence?mentioning
confidence: 99%
“…As was the case with eDNA transport, much of study of eDNA persistence has been motivated by concern over the release of transgenes from genetically modified organisms. Such studies have examined persistence of genes from transgenic crops in terrestrial soils (Widmer et al 1996(Widmer et al , 1997Hay et al 2002;Gebhard and Smalla 2006) and nearby groundwater and riverine environments (Matsui et al 2001;Zhu 2006). Across these studies, transgenic material remained detectable for long periods of time (days to years) in terrestrial soils, but much shorter periods of detection (hours to days) occurred in aquatic environments (Table 1).…”
Section: Fate: What Factors Influence Edna Persistence?mentioning
confidence: 99%
“…Mainly two aspects of natural transformation in the environment have been studied: the persistence of free DNA, and the ability of different bacterial species to become competent and take up free DNA under environmental conditions. Different studies have shown that in spite of the ubiquitous occurrence of DNases, highmolecular free DNA could be detected and its persistence in different environments has been demonstrated (Gebhard and Smalla, 1999;Nielsen et al, 1997;Paget and Simonet, 1997;Widmer et al, 1996;. Natural transformation is considered to also be the mechanism by which competent bacteria could capture DNA from transgenic plants (de Vries and Wackernagel, 1998;2004;Gebhard and Smalla, 1998).…”
Section: Natural Transformationmentioning
confidence: 99%
“…A more rapid breakdown of DNA was observed at higher soil H. Heuer and K. Smalla humidity and temperature. Both factors are thought to contribute to a higher microbial activity in soil (Blum et al, 1997;Widmer et al, 1996). In the study of Demanèche et al (2001a) plasmid DNA adsorbed on clay particles was found to be incompletely degradable even at high nuclease concentrations.…”
Section: Natural Transformationmentioning
confidence: 99%
“…L'absence de transgènes détectables dans le tractus digestif (Chambers et al 2001), les fèces (Harrison et al 1996;Netherwood et al 2004) ou les tissus (Chowdhury et al 2003a, b;Jennings et al 2003) d'animaux ou de sujets humains nourris de végétaux transgéniques suggère d'ailleurs une hydrolyse rapide de ces molécules, bien qu'incomplète sous certaines conditions (Chowdhury et al 2003a, b;MartinOrue et al 2002;Mercer et al 1999), au cours du processus de digestion alimentaire. En revanche, les molécules d'ADN pourraient montrer une certaine stabilité dans l'eau (Paul et al 1989) et une fraction non négligeable des molécules d'ADN relâchées des tissus végétaux dans le sol ne serait pas hydrolysée rapidement par les nucléases microbiennes et persisterait, adsorbée aux particules argileuses, sur des périodes suffisamment longues pour permettre l'inté-gration de ces molécules au génome d'éventuelles bactéries compétentes (Gebhard et Smalla 1999;Lorenz et Wackernagel 1992;Widmer et al 1996Widmer et al , 1997.…”
Section: La Persistance Des Transgènes Dans L'environnementunclassified